Considerations in applying the social relations model to the study of leadership emergence in groups: a leadership categorization perspective. - Hall, R.J.; Lord, R.G.; Foster, K.E. (Emerald, 2025)
This commentary on Kenny and Livi (2009) expands on aspects of leadership categorization theory that are consistent with the application of the social relations model (SRM). It critically considers limits to the generalization of the variance components analysis results described in Kenny and Livi's first example, and briefly summarizes results of an additional study that supports their findings. Finally, this commentary suggests interpretational issues of interest to researchers who wish to continue to apply the SRM to multi-level issues in the study of leadership.